Bolívar Echeverría: Philosophy and Utopia: (Fifteen years after his death) - Sigüenza, Javier (2025)
On July 23, 2025, in the Joaquín Gutiérrez Hall of the School of Letters at the UCR, a lecture was delivered by Dr. Javier Sigüenza. The lecturer, in addition to having been a research assistant to the renowned Ecuadorian-Mexican philosopher, is a specialist in his work and is in charge of the Bolívar Echeverría Archive. We offer the reader a slightly expanded version based on the discussion following the lecture, including the corresponding citations to the written text. Subsequently, we present Bolívar Echeverría’s address on the occasion of his appointment as Professor Emeritus at the UNAM in 2009. Although more than fifteen years have passed since the author delivered these words, his diagnosis of the Latin American university and the role of the Humanities in this century remains strikingly relevant. We reproduce this address, with permission from the Bolívar Echeverría Archive, as part of the tribute to this important critical theorist of our region carried out in the session with Dr. Sigüenza.